PHYSICAL ACTIVITY DOMAINS IN WOMEN OF THE SECOND MATURE PERIOD: COMPARATIVE IPAQ ANALYSIS - Fedyniak, N. V.; Vypasniak, I. P.; Soverda, I. Y. (Rehabilitation and Recreation, 2025)
Introduction. Data from international studies using the International Physical Activity Questionnaire (IPAQ) demonstrate considerable variability in overall physical activity (PA) among women in the second period of adulthood. Most studies indicate a decline in total PA after the age of 40. A substantial proportion of women (typically 20–40 %) are classified as having a “low” level of PA according to IPAQ, not reaching the minimum 600 MET-min/week. This can be attributed to both biological factors (menopause) and social changes (shift in roles and responsibilities). Menopausal symptoms, such as fatigue, sleep disturbances, hot flashes, and joint pain, act as direct physical barriers to initiating PA, leading women to prefer low-intensity activities to reduce discomfort.Objective. To assess domain-specific physical activity of women aged 36–45 years in the spheres of “Work/Study” and “Transportation”. Methods. The study employed theoretical analysis and literature review, sociological methods, and statistical analysis.Results. Total weekly energy expenditures at work or study were 7042.5 MET-min/week for women with normal posture, 2947.5 MET-min/week for those with round back, and 2539.5 MET-min/week for women with scoliotic posture. Thus, women with normal posture had the highest energy expenditures, while expenditures in the round-back and scoliotic groups were 58% and 64% lower, respectively. Statistical testing did not reveal significant differences between the three groups (p > 0.05). Nevertheless, analysis of medians and interquartile ranges highlighted clear trends: women with normal posture consistently demonstrated higher PA and energy expenditures. Conversely, postural deviations, such as round back or scoliosis, may limit range of motion, causing faster fatigue and necessitating compensatory efforts.Most participants reported regular motorized transport use approximately 4 days per week, with trips typically lasting around 45 minutes, though some trips were shorter and others lasted several hours. Walking was systematic: the majority of women walked 5–7 days per week for about 45 minutes, forming part of daily routines; for some, walking represented minor movements, while for others, it was a substantial component of total PA. The absence of cycling in the sample simplifies interpretation, as MET contributions for the “Transportation” domain were practically equivalent to walking. Average energy expenditures for walking were 1039.5 MET-min/week, closely matching total expenditures in the transportation domain (1157.7 MET-min/week). Hence, everyday mobility provided adequate energy output.Conclusions. The IPAQ is a valuable and practically indispensable tool for rapid population studies and for detecting trends in PA levels. However, its limitations in validity compared to objective methods necessitate, wherever possible, a combined approach and careful interpretation of results in the context of wartime and socio-economic constraints faced by women in the second period of adulthood in Ukraine.